Unveiling the Symphony of Economic Policies on Corporate Financial Performance: A Quantitative Revelation through SMARTPLS Analysis - Hapsari, Ambar Tri (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research investigates the influence of economic stimulus policy, fiscal policy, and the solvency risk of companies on their financial performance. Utilizing a quantitative approach, the study adopts regression analysis through SMARTPLS to analyze the data. Primary data for the variables - impact of economic stimulus policy, solvency risk of companies, and fiscal policy - were gathered, along with secondary data over a five-year period pertaining to the financial performance variable. The dataset was derived from 26 manufacturing companies listed on the Indonesia Stock Exchange (BEI). The findings reveal that both economic stimulus policy and fiscal policy exert a positive and significant effect on financial performance. In contrast, the solvency risk of companies does not exhibit a significant impact. This outcome suggests that while macroeconomic policies facilitate an environment conducive to financial growth, the internal risk management and financial structuring of a company play a critical role in leveraging these external benefits. The study underscores the importance of strategic internal management and effective risk mitigation practices in enhancing and sustaining financial performance amidst varying economic policies.